Characterization of T cell responses to co-administered hookworm vaccine candidates Na-GST-1 and Na-APR-1 in healthy adults in Gabon. - Yoanne D Mouwenda; Madeleine E Betouke Ongwe; Friederike Sonnet; Koen A Stam; Lucja A Labuda; Sophie De Vries; Martin P Grobusch; Frejus J Zinsou; Yabo J Honkpehedji; Jean-Claude Dejon Agobe; David J Diemert; Remko van Leeuwen; et al. (Public Library of Science (PLoS), 2021)
Two hookworm vaccine candidates, Na-GST-1 and Na-APR-1, formulated with Glucopyranosyl Lipid A (GLA-AF) adjuvant, have been shown to be safe, well tolerated, and to induce antibody responses in a Phase 1 clinical trial (Clinicaltrials.gov NCT02126462) conducted in Gabon. Here, we characterized T cell responses in 24 Gabonese volunteers randomized to get vaccinated three times with Na-GST-1 and Na-APR-1 at doses of 30μg (n = 8) or 100μg (n = 10) and as control Hepatitis B (n = 6). Blood was collected pre- and post-vaccination on days 0, 28, and 180 as well as 2-weeks after each vaccine dose on days 14, 42, and 194 for PBMCs isolation. PBMCs were stimulated with recombinant Na-GST-1 or Na-APR-1, before (days 0, 28 and 180) and two weeks after (days 14, 42 and 194) each vaccination and used to characterize T cell responses by flow and mass cytometry. A significant increase in Na-GST-1 -specific CD4+ T cells producing IL-2 and TNF, correlated with specific IgG antibody levels, after the third vaccination (day 194) was observed. In contrast, no increase in Na-APR-1 specific T cell responses were induced by the vaccine. Mass cytometry revealed that, Na-GST-1 cytokine producing CD4+ T cells were CD161+ memory cells expressing CTLA-4 and CD40-L. Blocking CTLA-4 enhanced the cytokine response to Na-GST-1. In Gabonese volunteers, hookworm vaccine candidate, Na-GST-1, induces detectable CD4+ T cell responses that correlate with specific antibody levels. As these CD4+ T cells express CTLA-4, and blocking this inhibitory molecules resulted in enhanced cytokine production, the question arises whether this pathway can be targeted to enhance vaccine immunogenicity.